The articulation of protest in Marguerite Porete's 'The mirror of simple souls' - Hassim, Leila Zanobiah (My University, 2016)
The focus of the thesis is on the counter-cultural comments and formulations in the medieval text The Mirror of Simple Souls by Frenchwoman Marguerite Porete, who suffered execution at the stake in 1310. The thesis demonstrates how in the past and into the current reading world the text can be seen as a form of literary protest/activism. The theoretical energies for the thesis draw from accounts of the medieval female experience, and the analysis is part empirical, part Marxist-feminist and part deconstructive. The broader context explores what literary protest/activism could have meant in medieval contexts and the gender strategies that were employed. The verbal texture of the book receives sustained attention as do the power relations between the dramatis personae, and the interplay between author and translator and (un)intended audience/reader(s) is explored, particularly shifts between presumed laity and expert theological influences and audiences.
Submitted in fulfilment of the requirements of the degree of MA at the University of the Witwatersrand. February 2015